2014
DOI: 10.3389/fnhum.2014.00159
|View full text |Cite
|
Sign up to set email alerts
|

Loss of form vision impairs spatial imagery

Abstract: Previous studies have reported inconsistent results when comparing spatial imagery performance in the blind and the sighted, with some, but not all, studies demonstrating deficits in the blind. Here, we investigated the effect of visual status and individual preferences ("cognitive style") on performance of a spatial imagery task. Participants with blindness resulting in the loss of form vision at or after age 6, and age-and gender-matched sighted participants, performed a spatial imagery task requiring memori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
8
1
Order By: Relevance
“…This contrasts with our earlier study of later-onset blindness (after age 6), in which performance on a spatial imagery task, similar to the present one except in using a 4 × 4 lettered matrix, was impaired in the late-blind compared to the sighted, independently of the age at which form vision was lost (Occelli et al, 2014). That the congenitally blind were not significantly worse than the sighted suggests that visual experience may not be necessary for the development of proficient spatial imagery or spatial memory.…”
Section: Discussioncontrasting
confidence: 99%
“…This contrasts with our earlier study of later-onset blindness (after age 6), in which performance on a spatial imagery task, similar to the present one except in using a 4 × 4 lettered matrix, was impaired in the late-blind compared to the sighted, independently of the age at which form vision was lost (Occelli et al, 2014). That the congenitally blind were not significantly worse than the sighted suggests that visual experience may not be necessary for the development of proficient spatial imagery or spatial memory.…”
Section: Discussioncontrasting
confidence: 99%
“…The neural basis of mental imagery within the intact auditory and haptic domains has been little researched in congenitally blind. The few studies that investigated haptic imagery focused on spatio-haptic tasks (Cattaneo et al 2007;Bonino et al 2008;Cornoldi et al 2009;Occelli et al 2014), or Braille reading (Heller 1989a;Buchel et al 1998;Cohen et al 2010;Striem-Amit et al 2012a). Auditory working memory studies showed superior performance in early blind (Roder et al 2001), which may be founded in superior encoding and consolidation (Stevens and Weaver 2005;Rokem and Ahissar 2009).…”
Section: Introductionmentioning
confidence: 99%
“…First, the relatively small sample size (12 blind and 18 sighted participants) in the present study may limit the reliability and generalizability of the behavioral and neural effects obtained. Second, while we relied on the notion that the long-term deprivation of visual inputs compromises visuospatial memory in the late-blind 29 , 30 , it should be further explored in future research how far residual visual memory contributes to word processing in those people. Third, our sample might consist of a heterogeneous group of blind participants since two of them had some experience in Braille reading.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore possible that, even in adulthood, motor codes of writing exert beneficial effects on word learning when visual or auditory sensory inputs are restricted. In particular, while the crossmodal interaction between the visual and phonological systems is thought to play a primary role in adult word learning 27 , 28 , such learning mechanism enhanced by literacy should be compromised by the long-term deprivation of visual inputs in the late-blind, which can attenuate visual memory retrieval 29 , 30 but may allow more cognitive resources for exploiting motor codes during word learning. We thus hypothesized that Exner’s area involved in the motor memory for handwriting should play a greater role in word learning for those blind people than for sighted people.…”
Section: Introductionmentioning
confidence: 99%